2015
DOI: 10.1021/acs.orglett.5b00953
|View full text |Cite
|
Sign up to set email alerts
|

Arene Oxidation with Malonoyl Peroxides

Abstract: Malonoyl peroxide 7, prepared in a single step from the commercially available diacid, is an effective reagent for the oxidation of aromatics. Reaction of an arene with peroxide 7 at room temperature leads to the corresponding protected phenol which can be unmasked by aminolysis. An ionic mechanism consistent with the experimental findings and supported by isotopic labeling, Hammett analysis, EPR investigations and reactivity profile studies is proposed.The oxidation and functionalization of hydrocarbons is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Interestingly, it has been shown that fluorinated alcohols can be used to accelerate reactions involving peroxides. 50,51 It has also been shown that fluorinated alcohols have the ability to activate hydrogen peroxide, 52 which has been specifically exploited in oxidation reactions. Examination of hexafluoroisopropanol (HFIP) as an alternative reaction solvent resulted in an equivalent conversion of cyclohexanone 4 to the ester 5 (42%; entry 12).…”
Section: Optimization Of the Baeyer-villiger Reactionmentioning
confidence: 99%
“…Interestingly, it has been shown that fluorinated alcohols can be used to accelerate reactions involving peroxides. 50,51 It has also been shown that fluorinated alcohols have the ability to activate hydrogen peroxide, 52 which has been specifically exploited in oxidation reactions. Examination of hexafluoroisopropanol (HFIP) as an alternative reaction solvent resulted in an equivalent conversion of cyclohexanone 4 to the ester 5 (42%; entry 12).…”
Section: Optimization Of the Baeyer-villiger Reactionmentioning
confidence: 99%
“…Similar outcomes were obtained when alternative silanes at C4' were tested in the reaction. Earlier iterations of the route featuring a late-stage sp 2 C-H oxidation at C4' using Ru catalysis 33 or peroxide-based reagents 34,35 also failed to deliver the desired product. As a workaround, silane 27 was first subjected to desilylative iodination with NIS to provide 28.…”
Section: While Indole Hydrogenation Typically Requires High H2mentioning
confidence: 99%
“…It has been known for more than six decades that a cyclic diacyl peroxide, initially phthaloyl peroxide, achieved mild and stereoselective 1,2‐dioxygenation of alkenes . A recent renaissance in this area has focused on malonoyl peroxides (1,2‐dioxa‐3,5‐diones), which accomplish number of unique transformations under mild and metal‐free conditions: syn‐ or anti‐ dioxygenation of alkenes;, syn dioxygenation/oxidative dearomatization of e‐rich arenes; monooxygenation of arenes and C‐H activation of heteroarenes;, chemoselective oxidation of divalent sulfur; and, oxygenation of enol ethers and dicarbonyls , . We note that diacyl peroxides should be used with caution.…”
Section: Related Compoundsmentioning
confidence: 99%